Osteoblast-specific expression of growth hormone stimulates bone growth in transgenic mice. - Baker, A R (1992)
Growth hormone (GH) is an important regulator of postnatal growth, acting on a wide variety of target tissues. Here, we show that local production of GH in osteoblasts is able to stimulate bone growth directly without significant systemic effects. Mice were made transgenic by microinjection of an osteocalcin-human GH (osteocalcin-hGH) gene construct in which approximately 1,800 bp of the rat osteocalcin promoter was fused to the hGH gene. Five lines of transgenic mice, each with measurable amounts of serum hGH (ranging from 1 to 1,000 ng/ml), were analyzed. Northern (RNA) blot hybridization showed that the hGH transcript was detectable only in the bone. Further characterization of hGH mRNA distribution by in situ hybridization revealed that in neonates the most intense signal was found in periosteal osteoblasts, while in adults, trabecular and endosteal osteoblasts were favored. In one transgenic line (992-1), hGH was expressed at a much lower level and had minimal systemic effects; however, the local concentrations of hGH in bone were sufficient to stimulate bone growth in these animals.